Peak alpha frequency is linked to visual temporal attention in 6-month-olds - Martina Arioli; Matteo Mattersberger; Stefanie Hoehl; Alicja Brzozowska (Scientific Reports)
Abstract The temporal resolution of adults’ visual attention has been linked to the frequency of alpha-band oscillations in electroencephalogram (EEG) signal, with higher Peak Alpha Frequency (PAF) being associated with better visual temporal processing skills. However, relatively less is known about neural mechanisms underlying individual differences in the temporal resolution of visual attention in infancy. This study investigated the role of PAF in visual temporal processing in early infancy. In a sample of 6-month-old infants (n = 62) we examined the relationship between PAF extracted from resting-state EEG, and saccadic latencies in a predictive cueing task where the appearance of a reward was predicted by higher or lower frequency of two flickering objects. Results showed that higher PAF was associated with shorter saccadic latencies in a condition with higher differences between the two flickering frequencies, speaking for the involvement of PAF in visual temporal attention in early development. Additionally, we found that infants were generally faster to orient to the reward in trials where both peripheral stimuli were flickering at relatively lower frequencies, roughly corresponding to the theta frequency band. Our findings support theoretical accounts highlighting the role of PAF in visual attention processing and extend this framework to early infancy.